PERANAN ORANG TUA DAN GURU DALAM EDUKASI SEKSUAL PADA ANAK KELAS 1 SDN 1 JERUK - Sayekti, Wulan Sri; Sayekti, Ika Candra (STIT AL MULTAZAM, 2024)
Sexual education in early childhood is crucial for the overall well-being of children. This research aims to explore the roles of parents, teachers, and the challenges they face in guiding their children on fundamental aspects of sexual education. The research adopts a qualitative approach, involving in-depth interviews with parents and teachers, as well as classroom observations. Findings reveal that parents and teachers at SDN 1 Jeruk play central roles in imparting information about the body, privacy, and values related to healthy sexual behavior to their children. Parental involvement primarily revolves around open discussions and the use of age-appropriate language. Meanwhile, teachers focus on the foundational material of sexual education in the curriculum and employ suitable teaching methods for first-grade students. However, several challenges are identified, such as parental knowledge limitations and teachers' concerns about parental reactions. This research provides profound insights into the efforts of parents and teachers in delivering sexual education to first-grade students. The implications of these findings can serve as a foundation for the development of more effective and supportive sexual education programs for young children in both school and family environments.